The Determinants of Financial Distress in Emerging Country: Empirical Evidence from Indonesia - Rathria Arrina Rachman (Jurnal Keuangan dan Perbankan, 2022)
This research strives to foresee corporate financial distress by applying three different perspectives that cover firms’ internal and external conditions namely accounting-based, market-based and macroeconomic models. Financially distressed and non-distressed corporations are analyzed using binomial logistic regression. Seven different models are employed to observe the effects of ten independent variables on financial distress, as well as to predict more accurately the possibility of firms defaulting. By exploring 257 public corporations listed on the Indonesia Stock Exchange over 10 years and utilizing 2,570 observations, the main finding suggests that when the accounting, market, and macroeconomic models are combined, it provides a better understanding of corporate failure than either model. Moreover, the results also indicate five factors that significantly determine the likelihood of a company’s financial distress: liquidity, profitability, asset productivity, market capitalization, and leverage. Accordingly, companies should keep a close watch on their accounting ratios and market indicators carefully to avoid bankruptcy. This research contributes to the finance and economic literature by paving the way for the development of an alternative perspective for predicting corporate failure in emerging markets.